Conductive hot melt adhesive with near-infrared light welding characteristic and preparation method thereof
By using conductive hot melt adhesive composed of gallium indium liquid metal, lipoic acid and multivalent crosslinking agent, the problem of traditional conductive adhesive in electronic component assembly is solved, and effective bonding and conductivity maintenance to multiple substrates is achieved.
Patent Information
- Application Number
- CN202411827744.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing conductive adhesives have problems such as corrosion, low solder joint strength, fatigue of solder joints, cracking and contamination caused by internal stress in the assembly of electronic components, and traditional contact heating methods are likely to cause damage to electronic components or substrates.
The conductive hot melt adhesive containing gallium indium liquid metal, lipoic acid and multivalent crosslinking agent is used to achieve effective bonding to various materials through heating or near-infrared light irradiation, and maintain electrical conductivity.
Effective bonding to a variety of solid substrates is achieved, conductivity is maintained, suitable for packaging and bonding of electronic components and components, and welding problems in traditional methods are avoided.
Smart Images

Figure CN119639415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material science and technology, and in particular to a conductive hot melt adhesive with near-infrared light welding characteristics and a preparation method thereof. Background Art
[0002] The progress of contemporary electronics and informatization has continuously promoted the development of electronic devices towards high integration, miniaturization, lightweight and high performance, which has brought new challenges to the assembly technology of high-density electronic devices. Electronic components, circuit connections and chip packaging usually use traditional metal welding technology, which faces problems such as easy corrosion, low solder joint strength, solder joint fatigue, cracking caused by internal stress of interconnects, and pollution. For this reason, the world is vigorously developing new bonding technology based on conductive adhesive to replace traditional metal welding. Conductive adhesive is a functional adhesive that has both conductivity and adhesiveness. It is usually composed of two parts: a viscous polymer resin matrix (generally epoxy resin, silicone, polyamide and polyurethane) and a conductive filler (such as metal, carbon material, conductive polymer, etc.). Conductive adhesives can establish effective bonding with different substrates, including bonding with non-solderable surfaces such as ceramics and glass. Therefore, they are favored in various application scenarios such as assembly, connection, integration, and packaging of integrated microelectronic products (Zhang D, Liu S, Jiang Y, et al. A flexible adhesive with a conductivity of 5240S / cm[J]. Science bulletin, 2021, 66(7): 657-660. Pang Kaimin, Deng Zuozhu. A conductive silver adhesive and its preparation method and application: 202211231498[P]. Haque ABMT, Ho DH, Hwang D, et al. Electrically conductive liquid metal composite adhesives for reversible bonding of soft electronics[J]. Advanced Functional Materials, 2023: 2304101.). At present, the bonding methods of conductive adhesives mainly include pressure-sensitive tape bonding, glue coating or heated melt coating (Zhang Jiuyang, Li Yan. A conductive hot melt adhesive and its preparation method: 202210288276[P]. Latko- P, Misiak M, Boczkowska A. Electrically conductive adhesive based on thermoplastic hot melt copolyamide and multi-walled carbon nanotubes[J]. Polymers, 2022, 14(20): 4371.). However, pressure-sensitive tape is limited by its low bonding strength and is only used as a coating material. The curing time of the glue coating bonding method is long and the use environment is limited, making it difficult to apply it to the bonding of microelectronic components with highly limited spatial dimensions. The melt coating of conductive hot melt adhesive is the main bonding method used in electronic component assembly, that is, the conductive adhesive is contact-heated at the welding point, and the electronic components, leads or high-density circuits are bonded after the conductive adhesive is melted. This contact heating method is very likely to cause damage to the electronic components or substrates around the conductive adhesive, and needs further improvement.
[0003] Therefore, providing a conductive hot melt adhesive with good conductivity and near-infrared light welding properties that can achieve effective bonding to a variety of solid substrates through infrared light irradiation and a preparation method thereof is a technical problem that technical personnel in the field urgently need to solve. Summary of the invention
[0004] In view of this, the present invention provides a light-weldable conductive hot melt adhesive containing liquid metal and a preparation method thereof. The conductive hot melt adhesive can effectively bond a variety of materials under heating or near-infrared light irradiation and maintain its conductivity, and can be applied to the fields of packaging and bonding of electronic components and assemblies.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The invention discloses a conductive hot melt adhesive with near-infrared light welding characteristics, which is composed of the following raw materials: gallium-indium liquid metal, thioctic acid and a multivalent cross-linking agent.
[0007] Preferably, the above-mentioned conductive hot melt adhesive with near-infrared light welding characteristics is composed of the following raw materials in percentage by mass: 65%-75% of gallium-indium liquid metal, 22.5%-27.5% of lipoic acid, and 2.5%-7.5% of a multivalent cross-linking agent.
[0008] Furthermore, the mass fraction of gallium in the gallium-indium liquid metal is 75.5% to 100%, and the mass fraction of indium is 24.5% to 0%.
[0009] The beneficial effect of adopting the above further scheme is that in the above scheme of the present invention, especially when the mass fraction of gallium in the gallium-indium liquid metal is 75.5% and the mass fraction of indium is 24.5%, its melting point is close to 25°C, which is conducive to application.
[0010] Furthermore, the gallium-indium liquid metal can be replaced by silver nanosheets or silver nanowires.
[0011] Furthermore, any one or more of the multivalent cross-linking agents selected from tannic acid, polyvinyl alcohol, N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and chitosan are mixed.
[0012] The beneficial effect of adopting the above further scheme is that the present invention can prepare conductive hot melt adhesives with different properties by adjusting the types and contents of conductive fillers and multivalent cross-linking agents, which reflects the universality and performance adjustability of the process of the present invention.
[0013] Furthermore, the light source for optical welding is near-infrared light, the power of the light source is 0.5-2.0 W, and the wavelength of the near-infrared light is 780-1100 nm.
[0014] Furthermore, the distance between any light source and the conductive hot melt adhesive during the optical welding process is 2.5-10.0 cm.
[0015] The beneficial effect of adopting the above further scheme is that the present invention can adjust the melting time of the conductive hot melt adhesive and the temperature of the light source irradiation point by adjusting the light source power and the distance between the light source and the conductive hot melt adhesive, so that the conductive hot melt adhesive is suitable for a variety of application scenarios.
[0016] The present invention also provides a method for preparing the above-mentioned conductive hot melt adhesive having near-infrared light welding characteristics, comprising the following steps:
[0017] (1) Weighing each raw material according to the above mass percentage;
[0018] (2) mixing gallium-indium liquid metal, thioctic acid and a multivalent crosslinking agent in an agate mortar and grinding to obtain a precursor powder;
[0019] (3) The precursor powder is heated to obtain a conductive hot melt adhesive having near-infrared light welding properties.
[0020] Furthermore, the grinding time in step (2) is 15-25 min.
[0021] Furthermore, in step (2), the heating temperature is 75-85° C., and the heating time is 25-35 min.
[0022] Furthermore, the heating is any one of an oil bath, a water bath, an air bath and a metal bath.
[0023] The beneficial effect of adopting the above further scheme is that the above scheme of the present invention can make the raw materials mixed evenly and the reaction as thorough as possible.
[0024] The beneficial effects of the present invention are as follows: the present invention discloses a conductive hot melt adhesive with optical welding characteristics formed based on a metal conductive component, thioctic acid and a multivalent crosslinking agent and a preparation process thereof. The obtained conductive hot melt adhesive has good electrical conductivity and can achieve effective bonding to a variety of solid substrates through near-infrared light irradiation.
[0025] The present invention uses thioctic acid, a multivalent cross-linking agent, and a metal conductive component as raw materials, first grinds the three raw materials through solid phase to obtain a precursor powder, and then heats the precursor powder to prepare a conductive hot melt adhesive with near-infrared light (808nm) welding characteristics. The preparation process of the conductive hot melt adhesive of the present invention is simple, the conditions are mild, and the time is short. It is an energy-saving, green, and environmentally friendly synthesis method. The obtained conductive hot melt adhesive can be processed into different shapes for storage (such as amorphous powder, microspheres, blocks, etc.), and different substrates can be adhered by direct heating or near-infrared light irradiation when necessary, and good bonding performance can be exhibited after curing at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The photographs are solid powders of liquid metal, lipoic acid and tannic acid before and after grinding in Example 1 of the present invention, and a digital photograph of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive formed by heating the ground powder;
[0027] Figure 2 This is a digital photograph of the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive prepared in Example 1 of the present invention being able to conduct electricity after being solidified and formed in a mold and connected to a circuit;
[0028] Figure 3 This is a digital photograph of the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive prepared in Example 1 of the present invention being bonded to different solid substrates;
[0029] Figure 4 This is a bar graph showing the shear tensile strength of the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive prepared in Example 1 of the present invention bonded to different solid substrates;
[0030] Figure 5 This is a digital photograph of the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive prepared in Example 1 of the present invention welding an LED lamp in a circuit under near-infrared light irradiation to form an effective loop. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the embodiments of the present invention, the liquid metal specifically refers to gallium-indium liquid metal composed of 75.5% gallium and 24.5% indium.
[0033] Example 1
[0034] 140 mg of liquid metal, 50 mg of lipoic acid, and 10 mg of tannic acid were placed in an agate mortar and ground for 20 min at 25 °C to obtain a precursor powder. Subsequently, the precursor powder was placed in a 3 mL glass bottle and heated in an 80 °C oil bath for 30 minutes to obtain a black viscous glue.
[0035] Figure 1 These are photos of solid powders of liquid metal, lipoic acid and tannic acid before and after grinding, as well as digital photos of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive formed by heating the ground powder. From the figure, it can be seen that after the ground powder sample is heated to 80°C, the sample changes from a powder to a sticky colloid that can be drawn, indicating that a hot melt adhesive is formed.
[0036] Test Example 1 Conductivity Test
[0037] The powder sample of the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive prepared in Example 1 was placed in a polytetrafluoroethylene mold with a size of 1.5 cm×1.5 cm×0.05 cm (length×width×height), first heated to 80°C to make it evenly spread in the mold, and then naturally cooled to 25°C to solidify for 10 minutes. The conductivity of the obtained block at 25°C was measured by RTS-9 four-probe tester to be 2×10 4 S / m, indicating that the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive obtained by the present invention has good conductivity.
[0038] Figure 2 This is a digital photo of the prepared liquid metal / lipoic acid / tannic acid conductive hot melt adhesive being able to conduct electricity after being solidified in a mold and connected to a circuit; from the figure, it can be seen that the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive can form an effective conductive path after being solidified and connected to a circuit, indicating that it has conductivity.
[0039] Test Example 2 Adhesion Test
[0040] The liquid metal / lipoic acid / tannic acid conductive hot melt adhesive powder prepared in Example 1 was placed on a nitrile glove and heated to 80°C by 808nm near-infrared light irradiation. Subsequently, objects of different materials (including glass beakers, agate mortar rods, stainless steel weights, Teflon reagent bottles, wooden substrates and shells, etc.) were pressed on the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive on the surface of the nitrile glove. When cooled to 25°C, the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive can be cured to form an effective bond, and the above bonded objects can be lifted, indicating that the obtained conductive hot melt adhesive has good adhesion.
[0041] In this test example, a single-column universal material testing machine was used to measure the lap shear strength of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive on different substrates. First, the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive powder was placed on the surface of two substrates of the same material (stainless steel, titanium, polycarbonate, polypropylene, length × width 7 × 1.3 cm). Secondly, the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive was heated to 80°C in an air bath, and any two substrates of the same material were bonded together in an overlapping manner, with an overlap length of 2 cm, and the thickness of the adhesive layer was controlled to 500 μm with a steel needle. Subsequently, the bonded substrates were cooled to 25°C in air and cured for 1h to measure their lap shear strength. Finally, the two ends of the solid substrate were vertically fixed on the electronic universal material testing machine and longitudinally stretched at a speed of 10 mm / min, and the maximum load force required when the bonded substrates were pulled apart under the load parallel to the adhesive layer at 25°C was measured, and the shear tensile strength was calculated based on the overlap area. The test results show that the lap shear strength of the obtained liquid metal / lipoic acid / tannic acid conductive hot melt adhesive on titanium, stainless steel, polycarbonate, and polypropylene substrates are 2.1±0.1MPa, 2.0±0.15MPa, 1.0±0.1MPa, and 0.52±0.04MPa, respectively.
[0042] Figure 3 This is a digital photo of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive bonding different solid substrates; from the picture, it can be seen that the conductive hot melt adhesive can bond solid objects of different materials and has obvious bonding ability.
[0043] Figure 4 This is a graph of the bonding shear tensile strength of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive to different solid substrates; from the figure it can be seen that the bonding strength of liquid metal / lipoic acid / tannic acid conductive hot melt adhesive to high surface energy substrates is greater than 1MPa, indicating that it has strong bonding strength.
[0044] Test Example 3 Light welding performance of conductive hot melt adhesive
[0045] Figure 5This is a digital photo of using liquid metal / lipoic acid / tannic acid conductive hot melt adhesive to weld LEDs in a circuit through near-infrared light and form an effective circuit; from the picture, it can be seen that the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive can weld the LED lamp to the copper sheet circuit under 808nm near-infrared light irradiation and light up the LED lamp when the battery power is turned on. The lit LED lamp did not flicker or fall off during the pulling of the wire, indicating that the liquid metal / lipoic acid / tannic acid conductive hot melt adhesive has light welding characteristics.
[0046] Example 2
[0047] According to the technical scheme of Example 1, the other conditions were kept unchanged, and 50 mg lipoic acid and 10 mg tannic acid were changed to 65 mg lipoic acid and 5 mg tannic acid to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 2.0±0.15MPa, 2.0±0.2MPa, 1.0±0.1MPa and 0.5±0.07MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0048] Example 3
[0049] According to the technical scheme of Example 1, the other conditions were kept unchanged, and 50 mg lipoic acid and 10 mg tannic acid were changed to 45 mg lipoic acid and 15 mg tannic acid to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 2.2±0.26MPa, 2.2±0.1MPa, 1.1±0.05MPa and 0.7±0.02MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0050] Example 4
[0051] According to the technical scheme of Example 1, the other conditions were kept unchanged, and the 140 mg liquid metal was replaced with 130 mg liquid metal and 10 mg silver nanowires to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.3×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.18MPa, 2.0±0.2MPa, 0.9±0.21MPa and 0.61±0.1MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0052] Example 5
[0053] According to the technical scheme of Example 1, the other conditions were kept unchanged, and the 140 mg liquid metal was replaced with 130 mg liquid metal and 10 mg silver nanosheets to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.5×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.1MPa, 2.0±0.14MPa, 0.8±0.12MPa and 0.58±0.08MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0054] Example 6
[0055] According to the technical scheme of Example 1, the other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 8 mg of polyvinyl alcohol (PVA) to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.1MPa, 1.8±0.1MPa, 0.94±0.11MPa and 0.55±0.02MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0056] Example 7
[0057] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 12.5 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 2.0±0.18MPa, 1.8±0.1MPa, 0.85±0.16MPa and 0.64±0.06MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0058] Example 8
[0059] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 11 mg of N,N,N',N'-tetrakis(2-hydroxyethyl) to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.2MPa, 1.8±0.17MPa, 0.98±0.14MPa and 0.60±0.05MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0060] Example 9
[0061] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of tannic acid and 5 mg of PVA to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.15MPa, 1.9±0.2MPa, 1.0±0.07MPa and 0.68±0.09MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0062] Example 10
[0063] According to the technical scheme of Example 1, the other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of tannic acid and 5 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.8±0.2MPa, 1.9±0.13MPa, 0.95±0.1MPa and 0.58±0.07MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0064] Embodiment 11
[0065] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of tannic acid and 5 mg of N,N,N',N'-tetrakis(2-hydroxyethyl) to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 2.0±0.1MPa, 2.1±0.13MPa, 1.2±0.2MPa and 0.75±0.08MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0066] Example 12
[0067] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of PVA and 5 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.9±0.11MPa, 1.9±0.15MPa, 0.97±0.1MPa and 0.62±0.04MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0068] Embodiment 13
[0069] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of PVA and 5 mg of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.8±0.12MPa, 1.7±0.2MPa, 0.86±0.1MPa and 0.51±0.07MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0070] Embodiment 14
[0071] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 5 mg of chitosan and 5 mg of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine) to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties, and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.7±0.15MPa, 1.7±0.2MPa, 0.84±0.1MPa and 0.52±0.02MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0072] Embodiment 15
[0073] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 3 mg of tannic acid, 3 mg of PVA and 4 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.8±0.2MPa, 1.9±0.2MPa, 1.0±0.1MPa and 0.7±0.09MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0074] Example 16
[0075] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 3 mg of tannic acid, 3 mg of PVA and 4 mg of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.8±0.13MPa, 1.8±0.1MPa, 1.0±0.1MPa and 0.73±0.03MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0076] Embodiment 17
[0077] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 3 mg of PVA, 3 mg of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and 4 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.0×10 4 S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.7±0.2MPa, 1.8±0.15MPa, 0.95±0.09MPa and 0.81±0.07MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0078] Embodiment 18
[0079] According to the technical scheme of Example 1, other conditions were kept unchanged, and 10 mg of tannic acid was replaced with 2.5 mg of tannic acid, 2.5 mg of PVA, 2.5 mg of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and 2.5 mg of chitosan to prepare a conductive hot melt adhesive. Then, the conductivity, tensile properties and photothermal properties of the conductive hot melt adhesive were tested according to the steps of the above test example. The conductivity test measured that the conductivity of the conductive hot melt adhesive was 2.1×10 4S / m. The lap shear of conductive hot melt adhesive on titanium, stainless steel, polycarbonate and polypropylene are 1.8±0.11MPa, 1.9±0.1MPa, 1.0±0.18MPa and 0.68±0.04MPa respectively. After the conductive hot melt adhesive is irradiated under a near-infrared lamp with a power of 0.5W and a wavelength of 808nm for 1min, a conductive hot melt adhesive with good bonding and conductivity can still be obtained.
[0080] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A conductive hot melt adhesive with near-infrared light welding properties, characterized in that: The invention is composed of the following raw materials: gallium-indium liquid metal, lipoic acid and a multivalent cross-linking agent.
2. The conductive hot melt adhesive with near infrared light welding characteristics according to claim 1, characterized in that: The invention is composed of the following raw materials in percentage by mass: 65%-75% of gallium-indium liquid metal, 22.5%-27.5% of thioctic acid and 2.5%-7.5% of a multivalent cross-linking agent.
3. The conductive hot melt adhesive with near infrared light welding characteristics according to claim 2, characterized in that: The mass fraction of gallium in the gallium-indium liquid metal is 75.5% to 100%, and the mass fraction of indium is 24.5% to 0%.
4. The conductive hot melt adhesive with near-infrared light welding properties according to claim 2, characterized in that: Any one or more of the multivalent cross-linking agents tannic acid, polyvinyl alcohol, N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and chitosan are mixed.
5. The conductive hot melt adhesive with near infrared light welding characteristics according to claim 2, characterized in that: The light source for optical welding is near infrared light, the power of the light source is 0.5-2.0W, and the wavelength of the near infrared light is 780-1100nm.
6. The conductive hot melt adhesive with near infrared light welding characteristics according to claim 5, characterized in that: During the optical welding process, the distance between any light source and the conductive hot melt adhesive is 2.5-10.0 cm.
7. A method for preparing a conductive hot melt adhesive having near-infrared light welding characteristics, characterized in that: The following steps are involved: (1) Weighing each raw material according to the mass percentage described in any one of claims 1 to 6; (2) mixing gallium-indium liquid metal, thioctic acid and a multivalent crosslinking agent in an agate mortar and grinding to obtain a precursor powder; (3) The precursor powder is heated to obtain a conductive hot melt adhesive having near-infrared light welding properties.
8. The method for preparing a conductive hot melt adhesive having near-infrared light welding characteristics according to claim 7, characterized in that: The grinding time in step (2) is 15-25 min.
9. The method for preparing a conductive hot melt adhesive having near-infrared light welding characteristics according to claim 7, characterized in that: The heating temperature in step (3) is 75-85° C. and the heating time is 25-35 min.
10. The method for preparing a conductive hot melt adhesive having near-infrared light welding characteristics according to claim 9, characterized in that: The heating is any one of an oil bath, a water bath, an air bath and a metal bath.
Citation Information
Patent Citations
Terpolymer adhesive containing lipoic acid anions and preparation method thereof
CN115353836A
Conductive ink, preparation method thereof and preparation method of wearable electronic device
CN119019890A
Hydrophilic skin adhesive
EP2886578A1
Process for jointing sealing and / or encapsulating an object
GB9909710D0
Thermosetting resin composition for bonding of semiconductor, and semiconductor device using the same
JP2013004868A